PENERAPAN MODEL TALKING STICK BERBANTUAN MEDIA RODA PUTAR PADA PEMBELAJARAN IPA SISWA KELAS V SD NEGERI 14 KOTA LUBUKLINGGAU - Sindi Purnama Sari; Novianti Mandasari; Fitria Lestari (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to determine the completeness of student learning outcomes after applying the Talking Stick learning model assisted by the Spinning Wheel media in science learning for fifth grade students at SD Negeri 14 Lubuklinggau City. The research method used is quasi-experimental. Data collection techniques in this study using tests. The test is in the form of multiple choice of 17 questions. Data analysis technique with steps: average score and standard deviation, normality test and z-test. The average score of the Pre-Test was 43.52 and the average value of the Post-Test was 76.72 with the percentage of students who completed 84%. Based on the z-test analysis, Zcount (3.48) and Ztable (1.64) are obtained when compared, Zcount > Ztable. For the final test at a significant level of α = 0.05, it can be concluded that the learning outcomes of the fifth grade students of SD Negeri 14 Lubuklinggau after the Talking Stick model with the aid of the Rotating Wheel media were significantly completed. Keywords: Encyclopedia, SBdP, Elementary School